2021
DOI: 10.1111/bdi.13052
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term lithium therapy and risk of chronic kidney disease in bipolar disorder: A historical cohort study

Abstract: Lithium (Li) is widely considered a first-line mood stabilizer for mania treatment and bipolar disorder (BD) maintenance. 1 The Li benefits have been demonstrated in several meta-analyses. 2,3 However, Li therapy is consistently underutilized in patients with BD and contributes to only 8% of the prescriptions for newly diagnosed BD in the United States. 4 The reasons for the reported underutilization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 46 publications
2
29
1
Order By: Relevance
“…Importantly, no tubulo-interstitial damage was detected in either aspirin (only) or aspirin and Litreated rats. Taking into account that long-term Li treatment duration is a risk factor for CKD [30][31][32][33][34][35][36][37][38][39], one possible explanation for the discrepancy between our results and those of Walker et al [148] could be the longer treatment duration in the Walker study (6 weeks vs. 24 weeks, respectively).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Importantly, no tubulo-interstitial damage was detected in either aspirin (only) or aspirin and Litreated rats. Taking into account that long-term Li treatment duration is a risk factor for CKD [30][31][32][33][34][35][36][37][38][39], one possible explanation for the discrepancy between our results and those of Walker et al [148] could be the longer treatment duration in the Walker study (6 weeks vs. 24 weeks, respectively).…”
Section: Discussioncontrasting
confidence: 88%
“…Factors that contribute to the development of NDI are elevated blood Li levels, long treatment duration, and high incidence of Li intoxication episodes [31]. Moreover, an unignorable body of data suggests that long-term use of Li increases the risk of chronic kidney disease (CKD) [30][31][32][33][34][35][36][37][38][39][40]. For example, Rej et al [32] found that Li is independently associated with an almost two-fold increase in CKD risk in elderly adults [32].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CKD development was relatively low in our study population, considering that the prevalence of CKD stage 3 in the general population of Korea was 7.9% in the national survey of 2011–12 and the prevalence of CKD stage 3–4 (6.9%) in the US population (Ji and Kim 2016 ; Murphy et al 2016 ), Previous studies in western environments have also reported higher CKD prevalence of 21–55% in long-term lithium users (Lepkifker et al 2004 ; Bendz et al 2010 ; Tredget et al 2010 ; Aiff et al 2014 ). The relatively lower age and shorter treatment duration in our study might have affected study findings (vs. mean age of 39.3 ± 16.0 years and mean duration on lithium of 3.5 ± 3.5 years in our study) (Pahwa et al 2021 ).…”
Section: Discussionmentioning
confidence: 53%
“…Considering the above findings, not only lithium treatment duration, 3,4 but also type‐2 diabetes mellitus, 2 benzodiazepine use, 2 cardiovascular disease, 3 albuminuria, 4 hypertension, 4 hypothyroidism, 4 and microcysts 4 may possibly worsen renal function independently or moderate the risk of impaired renal function induced by lithium. In addition, the debate on the role of episodes of acute lithium toxicity as risk moderators is ongoing 3 .…”
mentioning
confidence: 90%
“…For example, Pahwa et al 2 reported that among 154 patients who received long‐term lithium treatment, 41 patients (27%) developed chronic kidney disease (CKD; eGFR of less than 60 ml/min/ 1.73 m 2 ). Type 2 diabetes mellitus and benzodiazepine use were independent predictors for CKD development in the survival analysis after controlling for age.…”
mentioning
confidence: 99%